TINGKAT DEPRESI PADA IBU POSTPARTUM DI PUSKESMAS MOROKREMBANGAN SURABAYA - Indriasari W, Sisilia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2017)
Postpartum depression is an after birth depression lasting for months and sometimes it is anunrealized disease. The birth of a baby should bring in special happiness for mothers. But, theyare not ready due to the unwell sleep and weigh loss. This research identified the description ofpostpartum women’s depression level at Puskesmas. This was a descriptive research withdepression level as the variable. The available research population of was 64 mothers coming toPuskesmas to check themselves and total population was 55 respondents. The data were collectedusing enclosed questionnaire. The results showed that 53 % experienced mild depression, 33 %had no depression, 9% had major depression and 5 % experienced moderate depression, Themothers’ depression level at Puskesmas arranged from moderate to severe. The Mother andChild was expected to provide education on the prevention and treatment of postpartumdepression in pregnant women’s class.